Implementation of Healthy Conversation Skills to support behaviour change in the Bukhali trial in Soweto, South Africa: A process evaluation - Catherine Elizabeth Draper; Gugulethu Mabena; Molebogeng Motlhatlhedi; Nomsa Thwala; Wendy Lawrence; Susie Weller; Sonja Klingberg; Lisa J. Ware; Stephen J. Lye; Shane A. Norris (Elsevier, 2022)
Background: To address the need for preconception health interventions in low- and middle-income countries, the Healthy Life Trajectories Initiative (HeLTI) was launched in Soweto, South Africa to optimise young women's physical and mental health to establish healthier trajectories for themselves and, where relevant, the next generation. As part of HeLTI trial, the Bukhali intervention utilises the Healthy Conversation Skills (HCS) approach to promote behaviour change with 18-28-year-old women. The aim of this article is to report on the process evaluation of implementing HCS, to identify implementation challenges, and make recommendations for HCS adaptations. Methods: Data were collected from intervention session records (participants' response to setting behaviour change goals, community health workers (CHWs) impression of their HCS use; n ​= ​7418), individual in-depth interviews with participants (n ​= ​35), focus groups (3) and debrief sessions (13) with CHWs who deliver the intervention. Results: The findings indicated that the HCS approach was not implemented as originally intended. Challenges were reported regarding participants' willingness to set behaviour change goals, and prioritise health and health behaviour change, as well as participants' exposure to trauma, influencing their ability to prioritise health behaviour change. While CHWs were able to identify strengths of the HCS approach, there were challenges with contextual adaptation, especially using HCS in a multilingual setting such as Soweto. Recommendations for contextual adaptations of the HCS approach in Soweto, South Africa include simplification of certain HCS tools, language adaptions for a multilingual setting, adapting training to fit in with time constraints of a trial, and adopting a trauma-informed perspective to health behaviour change. Conclusions: This article extends our understanding of challenges to health behaviour change for young women in a low-income setting, highlighting the role of trauma, and the need for a trauma-informed perspective to understand behaviour change in this context.(PACTR201903750173871, Registered March 27, 2019).